Torymus ventralis (Fonscolombe) and Torymus maculatus sp. n. from Finland, and Torymus maculosus sp. n. from Corfu, Greece (Hymenoptera: Chalcidoidea: Torymidae) - Vikberg, Veli (Entomologica Fennica, 2011)
Two new species of Torymus with maculated forewings are described: T. maculatus sp. n. from southern Finland and T. maculosus sp. n. from Corfu, Greece. Both species are related to Torymus ventralis (Fonscolombe). Findings of T. ventralis in Finland are presented. The species is known as a parasitoid of Planetella (Diptera: Cecidomyiidae), although no Torymus was reared from subterranean galls of Planetella sp. on Carex lasiocarpa Ehrh. (Cyperaceae) in Finland. The only parasitoids to emerge from these galls were Eurytoma truncata (Boheman) and Eupelmus vesicularis (Retzius).